PENGARUH LINGKUNGAN KERJA DAN KEPEMIMPINAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN (STUDI PADA PT. TRI KEESON UTAMA) - Adryan Septiady (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Work Environment, Leadership, Employee Productivity The purpose of this research is to find out how the work environment, leadership and employee productivity are. The research method used is descriptive associative research method. The population in this study were all employees of PT Tri Keeson Utama Garut and all employees were sampled as many as 93 respondents and the sampling itself used a saturated sample. Based on the results of the study obtained a value greater than the value of r table 0.207 and reliable because the value obtained is greater than the value of Cronbach's alpha of 0.600. From the correlation test results obtained information that the work environment has a strong influence on employee productivity with an r value of 0.768 and a coefficient of determination of 59.9%, then leadership has a strong influence on employee productivity with an r value of 0.758 and a determination coefficient of 57.8%. While the work environment and leadership on employee productivity together have a strong influence with an r of 0.826 and a coefficient of determination of 68.3% and the rest is influenced by other factors not examined.